2019
DOI: 10.1108/jec-11-2018-0097
|View full text |Cite
|
Sign up to set email alerts
|

Long and winding road?

Abstract: Purpose The purpose of this paper is to explore and analyse the barriers entrepreneurs with disabilities (EWD) face when establishing their own enterprises, as well as the supporting factors in starting and running a business. Design/methodology/approach This is an explorative study. Data were collected using semi-structured interviews with ten Hungarian entrepreneurs with physical disabilities or sight-loss, during the summer of 2018. Findings The paper classifies the barriers and supporting factors, as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…At a later stage in the process (see Selecting relevant studies, below), we discovered that barriers and opportunities were well researched and the knowledge synthesised (e.g. Csillag, Gyori, and Svastics 2019). However, we identified a gap when it comes to synthesising the knowledge of establishment motives.…”
Section: Research Questionmentioning
confidence: 93%
See 2 more Smart Citations
“…At a later stage in the process (see Selecting relevant studies, below), we discovered that barriers and opportunities were well researched and the knowledge synthesised (e.g. Csillag, Gyori, and Svastics 2019). However, we identified a gap when it comes to synthesising the knowledge of establishment motives.…”
Section: Research Questionmentioning
confidence: 93%
“…The reading yielded a total of 117 potentially relevant studies. In the process of reading all articles in full, we found that barriers and opportunities, both part of our initial research question, were well researched and the knowledge synthesised (Csillag, Gyori, and Svastics 2019). A reformulated research question focused on establishment motives among people with disabilities (see Research question, above).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest is the opinion of Roundy P, who argues that entrepreneurial ecosystems influence the activities and effectiveness of social entrepreneurs through mechanisms such as: the diversity of resource providers, the availability of support infrastructure and entrepreneurial culture, as well as available training opportunities [10]. Social entrepreneurs can not only form entrepreneurial ecosystems, but also attract attention to the created ecosystem of interested parties, thereby increasing its profitability [11,12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The company owner does not necessarily do this. However, according to Csillag et al (2019), it is caused by an unsupportive ecosystem, and there is still much stigma built up in a society that the abilities of people with disabilities are still far below those of non-disabled people.…”
Section: Introductionmentioning
confidence: 99%